Pemberdayaan Masyarakat melalui Peningkatan Keterampilan dan Produktivitas Usaha Peternakan Domba Berbasis IPTEK - Moh. Khoirul Fatih; Sutikno Sutikno (Al-Qalam Institute, 2023)
Kertosono Village is a village located in Sidayu District, Gresik Regency, Community Empowerment Through Improving Skills and Productivity of Science and Technology-Based Sheep Livestock Business is an effort to increase community skills and productivity in managing livestock business through fermentation technology. Most of the people's livelihood is farming and animal husbandry. The average population there owns livestock which are kept either in cage groups or kept around their homes. The main problem currently being faced is the limited productivity of the livestock business. Farmers still work individually and traditionally with limited knowledge and skills, and view livestock business as a side job. This is due to the lack of awareness, knowledge, and skills to utilize technology as a means of supporting improving skills and productivity of livestock business. The purpose of this empowerment is to improve the skills and productivity of the community in the manufacture of fermented feed technology, increase the types of livestock products and the quality of livestock products and modern marketing.